Chapel constructed by Rose Nesbit in 1787 - Mumbai Archive Project Team (Jio Institute, 2024)
St. Anne’s Church was built on the site of a chapel constructed in 1787 by Rose Nesbit, an Armenian lady. The chapel built by the Nesbit family was called Igreja da Senhora Santa Anna, named after the mother of Mary. In the 19th century, the Jesuits renamed it Saint Anne’s Church.